Strengthening the Institutional Response to HIV/AIDS/STI in the Caribbean (SIRHASC) : external mid-term review final report - Kerouedan, Dominique (CREDES ParisFR, 2004)
Describes the SIRHASC Project. Outlines the Mid-term review objectives, issues to be studied, methodology and tools. Focuses on the project's achievements and reviews the management and financial aspects. Analyzes the project with regard to relevance, effectiveness, outcomes, constraints, efficiency, strengths and weakness and sustainability. Concludes that the SIRHASC Project is an outstanding success story. Makes recommendations.